Strengthening Teachers’ Competencies in Utilising ICT in Physics Experiment Activities and Developing Student Worksheets - Ghaida Prinisa Achmad; Nur Aini; Misykah Aulia Anwar; Vivi Mardian; Siska Dewi Aryani; Ika Mustika Sari; Andi Suhandi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The development of ICT brings new innovations in physics learning. Thus, the application of ICT needs to be trained to be mastered by teachers in physics education. The community service aimed to strengthen teachers' competencies in utilising ICT and training in developing student worksheets for physics experiments. The software includes PhET, Physical Phone Experiment, and Physics Toolbox. The implementation method included preparation, implementation, and evaluation stages. The activities on the first day (online) included introducing technology-based software as laboratory support and designing student worksheets to train students’ skills. The activities on the second day (offline) involved direct training on software usage and student worksheet creation. On the third day (online), there were presentations of the student worksheets created by teachers. There were 110 participants in this community service, consisting of physics and science teachers from various Sumatera, Java, Kalimantan, and Sulawesi schools. The implementation of the community service utilised lectures, Q&A sessions, discussions, and demonstrations. The achievements of the community service included providing teachers with new knowledge and experiences in developing student worksheets. The validity results of the student worksheets created by teachers obtained an average percentage of 95.5%. This indicated that the community service activities positively impacted teachers and were highly effective.